Неінвазивні дослідження курганів в басейнах річок Мурафа та Рів на Вінниччині у 2019 році - Пшибила, М.; Рудь, В.С.; Шмит, М.; Влодарчак, П.; Журкєвіч, Д.; Потупчик, М.В. (Археологія і давня історія України, 2021)
У статті представлено результати геофізичних досліджень чотирьох курганних груп, розташованих у середній течії міжріччя Південного Бугу та Дністра. In 2019, the implementation of the first stage of
the field investigations within the project «Podolia as
a contact area in the 3rd millennium BC: Kurgans on
the rivers Murafa and Riv» began. The project is financed
by the National Science Centre, Poland, under
no. 2017/27/B/HS3/01444.
The main goal of the research is to identify the forms
and intensity of the intercultural contacts in the region
of the middle course of the Southern Buh and the Dnister
interfluve. The burial mounds, located between the
rivers Murafa (left-bank basin of the Dnister River) and
Riv (right-bank basin of the Southern Buh River), are
objects of the study. Professional archeological excavations
of the burial mounds in the region have not been
conducted before. There are only data about unauthorized
excavations of several burial mounds by locals at
the turn of the XIX—XX centuries, which perhaps contained
burials with artefacts of the Globular Amphora
culture. More than a century later, archaeologists conducted
registration of the burial mounds in the region.
M. Potupchyk has surveyed and mapped most of the
mound groups.
In the framework of the project realization, the
non-invasive geophysical studies of four burial mound
groups, located near the villages of Sloboda Noskovetska,
Tokarivka and Sloboda Mezhyrivska of Zhmerynka
district and between the villages of Ivanivtsi and Antonivka
of Bar district of Vinnytsia region were conducted.
The total obtained area is 8.19 hectares. Thirteen
burial mounds are located there.
A number of anomalies inside and outside the burial
mounds were found by magnetic survey. Most often,
anomalies form circular or square structures that surround
mound and can be interpreted as ditches. Mainly
in the central parts of the burial mounds, anomalies
of various shapes were also found. They appear to be
associated with burial objects. Sometimes anomalies
outside the burial mounds, but in close proximity to
them, are also interpreted as potentially archaeological
objects. The latter may be associated with a variety
of funeral rites. There were also burial mounds within
which no clear magnetic anomalies were observed.
This is probably also a reflection of the funeral traditions
and construction of the mounds.